Anti-inflammatory Role of Galectin-8 During Trypanosoma cruzi Chronic Infection - Bertelli, Adriano; Sanmarco, Liliana M.; Pascuale, Carla A.; Postan, Miriam; Aoki, Maria P.; Leguizamón, María S. (Frontiers in Cellular and Infection Microbiology, 2020)
Galectins are animal lectins with high affinity for β-galactosides that drive the immune response through several mechanisms. In particular, the role of Galectin 8 (Gal-8) in inflammation remains controversial. To analyze its role in a chronic inflammatory environment, we studied a murine model of Trypanosoma cruzi infection. This infection induces strong cardiac inflammation that, along with fibrosis, generates cardiomegalia and subsequently Chagas disease. By analysing infected wild type (iWT) and Gal-8 deficient (iGal-8KO) C57BL/6J mice at the chronic phase (4-5 months post-infection), we observed that the lack of Gal-8 favored a generalized increment of inflammation in liver, skeletal muscle and heart, followed by extended fibrosis, even without differences in tissular parasite loads. Remarkably, increased frequencies of neutrophils and macrophages were observed within cardiac iGal-8KO tissue. It was proposed that Gal-8, as well as other galectins, induce the surface expression of the inner molecule phosphatidylserine on activated neutrophils, which serves as an “eat-me” signal for macrophages, favoring viable neutrophil removal and tissue injury protection, a process known as preaparesis. We found that the increased rate of neutrophils could be associated to the absence of Gal-8-dependent preaparesis leading to a diminished neutrophil-clearing ability in macrophages. Thus, we conclude that Gal-8 exerts an anti-inflammatory role in chronic T.cruzi infection.